Implementation Government's Internal Control System on the Quality Financial Reporting Which Moderate by Human Resource Competency - Nasrun Naida (Medikun Publisher, 2024)
This study aims to (1) explain the implementation of Government Internal Control Systems (GICS), and Financial Report Quality; (2) assess the effect of LGIS implementation on Financial Report Quality (FRQ); (3) evaluate the influence of GICS implementation on FRQ; (4) identify how the interaction between LGIS and Human Resource Competence affects FRQ; and (5) analyze the interaction between GICS and Human Resource Competence on FRQ. The study employed Partial Least Square (PLS) method in Structural Equation Modeling (SEM) using WarpPLS 8.0 software, involving 128 respondents. Findings indicate that (1) the majority of Local Government Agencies (LGAs) support the use of LGIS and GICS to enhance FRQ; (2) LGIS has a positive and significant impact on FRQ; (3) GICS similarly has a positive and significant impact on FRQ; (4) Human Resource Competence strengthens the relationship between LGIS and FRQ; and (5) likewise enhances the relationship between GICS and FRQ